Evaluation of stock profile models for burden distribution in blast furnace. (November 2015) - Shi, P.Y.; Fu, D.; Zhou, P.; Zhou, C. Q.
Abstract : Burden distribution in a blast furnace is vital to its smooth running. Mathematical models have been applied to guide the charging process to achieve desired burden distribution. The accuracies of such models depend on the prediction of falling curve, stock profile and burden descent mode. Among them, the stock profile model greatly influences the final burden distribution. In this study, a special evaluation index for the accuracy of the modelled burden profile based on charging volume is established. Six existing stock profile models were evaluated and compared with the published experiment data of a scaled blast furnace. It is found that all the models predicted the stock profile well. However, certain models showed increased accuracy for the particular case.